تعيين الاهتزازات العرضانية اللاخطية لقضيب من مادة مرنة فعالة (Latakia University Journal -Basic Sciences Series, 2014)
إن الهدف من البحث المقدم في هذا العمل هو إيجاد طريقة موحدة لحل مسائل الاهتزازات العرضانية في الأوساط المرنة اللاخطية بوجود العامل البيولوجي. حصلنا على معادلات الاهتزازات العرضانية للمنظومات المرنة وذلك بالاعتماد على نماذج رياضية معروفة ثم حلينا  مسألة الاهتزازات التوافقية العرضانية لقضيب فعال مرن لاخطي منتهي الطول.The goal of the presented research in this paper is finding a unified way to solve cross vibration problems in nonlinear elastic fields with a biological factor. We obtained the equations of cross vibration for elastic systems by using known mathematical models, and then we solved the nonlinear cross harmonic vibration problem for a finite length of effective bar.